200 classic cartoons - Mill Creek Entertainment ([United States] : Mill Creek Entertainment, 2008)
A collection of cartoon shorts featuring Betty Boop, Popeye, Mr. Bang, Katrinka & the Skipper, Casper, Felix the Cat, and others.
Disc 4: Cartoons featuring Fraidy Cat, Gumby, Hoppity Hooper, Popeye, other classics.
Title from container.
Animated.
DVD.
Keywords: Animated films; Short films; Fiction films